EARLY LEFT VENTRICULAR GLOBAL LONGITUDINAL STRAIN DETERIORATION AFTER AORTIC ANEURYSM REPAIR IN HYPERTENSIVE PATIENTS: IMPACT OF AORTIC STIFFNESS. (April 2021) - Marketou, Maria; Papadopoulos, George; Kontopodis, Nikolaos; Patrianakos, Alexandros; Nakou, Elenh; Maragkoudakis, Spyros; Stratakis, Stavros; Tavlas, Emmanuel; Ioannou, Christos; Parthenakis, Fragiskos
Abstract : Objective: Invasive abdominal aortic aneurysm (AAA) replacement with an endograft interposes between the normal arterial tree which may acutely reduce overall systemic compliance. As a result, the input impedance is significantly increased, as are central systolic and pulse pressures. We evaluated changes in left ventricular global longitudinal peak strain (GLPS) in hypertensive patients undergoing repair of AAA in relation with the changes in arterial stiffness. Design and method: This was a single-center, nonrandomized, prospective, observational cohort study. Consecutive AAA hypertensive patients who underwent open or endovascular repair (EVAR) were enrolled. All patients were asymptomatic from their AAA and were admitted for elective treatment; there were no planned adjunctive procedures at the time of repair. A standard M-mode and 2-dimensional (2D) echocardiographic study was performed in all participants Left ventricular global longitudinal strain (GLS), and carotid-femoral pulse wave velocity (cf-PWV) were estimated 1 week preoperatively, as well as 1 and 6 months postoperatively.. Left ventricular global longitudinal strain (GLS), and carotid-femoral pulse wave velocity (cf-PWV) were estimated 1 week preoperatively, as well as 1 and 6 months postoperatively. Results: A total of 70 men, mean age 70 ± 7 years, were evaluated. Of these, 58 underwent EVAR and 12 open repair. A significant time effect was found on cf-PWV, which showed an increase at 1 month and remained thereafter (p = 0.006). Additionally, a deterioration in GLS values was revealed, with a significant increase at 1 month that persisted 5 months later (p < 0.001). No significant group effect was observed between EVAR and open repair (p = 0.98) and there was no significant interaction (p = 0.96). Notably, the difference of global longitudinal strain (DGLS) between baseline and 6 months significantly correlated with the corresponding changes in cf-PWV (r = 0.494, p < 0.0001). Conclusions: AAA repair may have detrimental effects in cardiac systolic function. Our findings highlight the need a more intense cardiac surveillance program after aortic reconstruction. Further studies are needed to investigate how this may translate into long-term manifestations of cardiovascular complications and symptomatology.